Nutritional Status Analysis of Grade 4A Students at SD 064981 Cempaka Raya Based on Height, Weight, and Snack Consumption Patterns - Sudana Fatahillah Pasaribu; Farhatun Nurha; Dhea Syafitri; Dwitri Amalia Susanti; Etika Lase; Febry Lesmana Putri; Tri Cahyani Lase (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
The nutritional status of elementary school children serves as a vital indicator of their overall growth, development, and future health outcomes. Poor nutritional status, whether in the form of undernutrition or overweight, can lead to a range of health and academic performance issues. This study aimed to assess the nutritional status of Grade 4A students at SD 064981 Cempaka Raya using anthropometric measurements and to examine the association between snacking habits and nutritional categories. A descriptive quantitative research design was employed, utilizing a total sampling approach involving all 20 students in the class. Data collection consisted of direct height and weight measurements conducted according to standardized procedures. The data were then analyzed using the WHO Anthro Plus software to classify nutritional status into undernourished, normal, overweight, and obese categories. Additionally, information on students’ snacking habits during school hours was obtained through structured questionnaires. The results indicated that 25% of students were undernourished, 50% had normal nutritional status, 20% were overweight, and 5% were obese. Bivariate analysis using the Chi-Square test demonstrated a statistically significant relationship (p < 0.001) between snacking behavior and nutritional status. Specifically, all students who reported frequent consumption of snacks at school were classified as overweight or obese, whereas those who did not engage in frequent snacking predominantly fell within the undernourished or normal categories. These findings highlight the potential role of unhealthy snacking patterns in contributing to excessive weight gain among school-age children. Based on the results, it is recommended that nutrition education programs be implemented for both students and parents, coupled with stricter regulations on the availability and sale of high-calorie snack foods within the school environment. Such measures may serve as preventive strategies to promote healthy growth, maintain optimal nutritional status, and reduce the risk of non-communicable diseases later in life.